Produktivitas Primer Perairan Kolong Bekas Tambang Bauksit di Kota Tanjungpinang, Kepulauan Riau - Apriadi, Tri; Putra, Risandi Dwirama; Idris, Fadhliyah (Indonesian Institute of Sciences, 2019)
Primary Productivity on Abandoned Bauxite Mining Pits of Tanjungpinang City, Riau Islands. The abandoned bauxite mining pits in Bintan Island have a good opportunity to be developed, especially as an aquaculture area. The objective of this study was to determine the primary productivity of the waters, phytoplankton ecological index, and physical and chemical parameters of the bauxite post-mining ponds in Tanjungpinang City, Riau Islands. The study was conducted in April-August 2018 in two bauxite post-mining ponds (station 1 and 2) in Senggarang, Tanjungpinang City. The parameters observed were the abundance and ecological index of phytoplankton, aquatic primary productivity, physical and chemical parameters of the waters, and nutrients, N and P. From the study it was found that there were three phytoplankton divisions, consisted of three classes and eight genera. Mougeotia sp. was the dominant species of phytoplankton. The abandoned bauxite mining pits were classified as labile and the phytoplankton communities were under environmental stress due to the dominance of certain species. The abandoned bauxite mining pits were classified as young (inundation <5 years), low primary productivity, as well as oligotrophic waters. Net primary productivity in station 2 was higher than station 1, i.e. 1,23 mgC L-1 day-1 and 0,25 mgC L-1 day-1, respectively. The physical and chemical parameters of the bauxite post-mining ponds studied met the quality standards for freshwater aquaculture activities, except for pH and ammonia.